THE EFFECT OF USING TIME TOKEN ON STUDENTS’ SPEAKING SKILL - Ramadhani, Fariza; Fauzana, Riri (Indonesian Journal of Integrated English Language Teaching, 2023)
This study aims to determine whether there is an effect of using Time Token     Arends on the speaking ability of eleventh grade students at SMK Negeri 1 Kandis. This study uses quantitative. The object of this research is to determine the effect of using Time Token Arends on students' speaking ability and the subject of this research is the eleventh grade in SMK Negeri 1 Kandis. Data were collected through an oral test. There were 23 eleventh grade students as a sample            at SMK Negeri 1 Kandis who participated in this study and randomly selected. Data analysis was analyzed descriptive statistical analysis. The findings show that learning using time tokens has a contribution of  31.25 to students' speaking ability. It means that there is a significant effect of the learning strategy by using time tokens on students' speaking ability. Keywords: Time Token, Speaking Skill